I cheerfully refuse : a novel - Enger, Leif (Grove Press, 2024)
"Set in a not-too-distant America, I Cheerfully Refuse is the tale of a bereaved and pursued musician embarking under sail on a sentient Lake Superior in search of his departed, deeply beloved, bookselling wife. Rainy, an endearing bear of an Orphean narrator, seeks refuge in the harbors, fogs, and remote islands of the inland sea. Encountering lunatic storms and rising corpses from the warming depths, Rainy finds on land an increasingly desperate and illiterate people, a malignant billionaire ruling class, crumbled infrastructure, and a lawless society. Amid the Gulliver-like challenges of life at sea and no safe landings, Rainy is lifted by physical beauty, surprising humor, generous strangers, and an unexpected companion in a young girl who comes aboard. And as his innate guileless nature begins to make an inadvertent rebel of him, Rainy's private quest for the love of his life grows into something wider and wilder, sweeping up friends and foes alike in his strengthening wake. I Cheerfully Refuse epitomizes the "musical, sometimes magical and deeply satisfying kind of storytelling" (Los Angeles Times) for which Leif Enger is cherished. A rollicking narrative in the most evocative of settings, this latest novel is a symphony against despair and a rallying cry for the future"--